Analisis Manajemen Pengelolaan Logistik Sediaan Farmasi dan Perbekalan Kesehatan di Instalasi Farmasi - Widy Susanti Abdulkadir; Madania Madania; Teti S. Tuloli; Nur Rasdianah; Juliyanty Akuba (Jurusan Farmasi Universitas Negeri Gorontalo, 2022)
Drug management is a set of optimally conducted activities related to the aspects of drug planning, procurement, storing, distribution, and extermination. This was done to achieve the proper drug amount, types, supply, maintenance, and medication. Earlier observstion revealed problems in managing pharmaceutical stock and consumables, where some of the stocks are empty. This qualitative descriptive research focus on identifying pharmaceutical logistic stock and health supplies comprising drug planning, procurement, storing, distribution, and extermination in the pharmaceutical unit of Gorontalo. The primary data were obtained from questionnaires based on technical guidance by the health ministry while the secondary were obtained from related documents. Based on the findings, the pharmaceutical stock planning and storing process at the pharmacy unit did not meet the health ministry standards, which is opposite to the procurement, distribution, and extermination process.